Crack-based serviceability assessment of post-tensioned segmental concrete box-girder bridges. (April 2021) - He, Zhi-Qi; Li, Yonghui; Xu, Tian; Liu, Zhao; Ma, Zhongguo John
Abstract: Post-tensioned segmental box-girders produce elegant and robust solutions for long-span concrete bridges. Concrete cracking and excessive long-term deflections would greatly impact the in-service performance of this type of structure. This study presents a crack-based approach for the serviceability assessment of cracked box-girders. It is presumed that the excessive prestress loss is the main cause for extensive cracking and excessive long-term deflections in long-span post-tensioned concrete bridges. The approach consists of crack-based mechanical models that link visual crack data to the structure's critical conditions. Procedures for the flexural-crack based and the shear-crack based assessments are established and applied in the condition evaluation of two real bridges. The proposed procedure employs visual concrete crack data as input, and it provides quantitative output of the in-service performance of cracked box-girders, such as the effective prestress of longitudinal and vertical prestressing tendons, the effective flexural and shear stiffnesses after cracking, and the development of long-term deflections.